Multiorgan dysfunction in a geriatric dog with congestive heart failure complicated by chronic kidney disease and uremic enteritis - Safitri, Widia; sary, Rahmadia; Primayani, Regina (ARSHI Veterinary Letters, 2026)
Congestive heart failure (CHF) in geriatric dogs may progress to multi-organ dysfunction, particularly affecting the renal and gastrointestinal systems. A 12-year-old male Golden Retriever presented with progressive dyspnea, nocturnal cough, vomiting, diarrhea, and weakness. Clinical examination revealed severe dyspnea with mild cyanosis. Hematology revealed mild anemia, leukocytosis, and thrombocytosis, whereas biochemistry revealed severe azotemia (urea 238.9 mg/dL; creatinine 14.85 mg/dL), indicating advanced chronic kidney disease. Thoracic radiography showed cardiomegaly with pulmonary edema, and abdominal radiography revealed intestinal gas distension, suggesting uremic enteritis. The patient received supportive care, including IV fluids, oxygen, antibiotics, and gastroprotective agents. Despite respiratory improvement, gastrointestinal bleeding persisted. The diagnosis was left-sided congestive heart failure with advanced chronic kidney disease and uremic enteritis. The prognosis was infausta. The patient was treated with four days of supportive therapy consisting of low-rate intravenous Ringer’s lactate, antibiotics, gastroprotectants, vitamin B-complex supplementation, and oxygen therapy.